Contrast-Enhanced Ultrasound Guided Biopsy of Undetermined Abdominal Lesions: A Multidisciplinary Decision-Making Approach. (4th January 2017) - Mao, Feng; Dong, Yi; Ji, Zhengbiao; Cao, Jiaying; Wang, Wen-Ping
Abstract : Aim. To investigate the value of contrast-enhanced ultrasound (CEUS) guided biopsy of undetermined abdominal lesions in multidisciplinary treatment (MDT) decision-making approach. Methods. Between Jan 2012 and Dec 2015, 60 consecutive patients (male, 37; female, 23; mean age, 51.3 years ± 14.6) who presented with undetermined abdominal lesions were included. CEUS and core needle percutaneous biopsy was performed under real-time CEUS guidance in all lesions. Data were recorded and compared with conventional ultrasound (US) guidance group (n = 75 ). All CEUS findings and clinical data were evaluated in MDT. Results. CEUS enabled the delimitation of more (88.3% versus 41.3%) and larger (14.1 ± 10.7 mm versus 32.3 ± 18.5 mm) nonenhanced necrotic areas. More inner (20.0% versus 6.7%) and surrounding (18.3% versus 2.7%) major vessels were visualized and avoided during biopsies. CEUS-guided biopsy increased the diagnostic accuracy from 93.3% to 98.3%, with correct diagnosis in 57 of 60 lesions (95.0%). The therapeutic plan was influenced by CEUS guided biopsies findings in the majority of patients (98.3%). Conclusion. The combination of CEUS guided biopsy and MDT decision-making approach is useful in the diagnostic work-up and therapeutic management.